Mental and self-rated health of bakery workers in Lebanon: A national study. (October 2020) - Habib, Rima R; El-Haddad, Nataly W; Elzein, Kareem; Hojeij, Safa
Objectives: The relationship between poverty and health has been well addressed in public health research. The health effects of social and economic inequalities on working groups have also drawn the attention of occupational health scholars. Research addressing workers in low-paying jobs showed increased risks for poor health. This research examined the psychosocial factors associated with poor mental health and self-rated health among low-income bakery workers performing demanding tasks. Methods: Face-to-face interviews in 504 randomly selected bakeries in Lebanon provided data on socio-demographics, perception of the workplace environment, job security, job satisfaction, general health, and mental health. Results: In total, 16.5% of bakery workers reported poor self-rated health, and 45% reported poor mental health. Workers with a chronic illness were almost three times more likely to report poor self-rated health (OR = 2.86; 95% CI = 1.44–5.67), and those with musculoskeletal pain reported poor self-rated health five times as often (OR = 5.34; 95% CI = 2.9–9.80). Those with a chronic illness and musculoskeletal pain were twice as likely to report poor mental health (OR = 1.94; 95% CI = 1.07–3.50 and OR = 2.07; 95% CI = 1.32–3.23, respectively); and those dissatisfied with their job reported poorer self-rated health (OR = 2.18; 95% CI = 1.12–4.23) and mental health (OR = 2.57; 95% CI = 1.54–4.26). In addition, workers reporting job insecurity had poor mental health twice as often (OR = 1.93; 95% CI = 1.24–2.99). Low socioeconomic indicators showed a gradient association with both poor self-rated health and mental health. Conclusion: Reporting job dissatisfaction and insecurity, musculoskeletal pain, and chronic illness were associated with poor mental and self-rated health among bakery workers. Interventions to improve the working conditions of bakery workers are timely and essential. This research provided evidence for policy to guide occupational health practice and safeguard the health of bakery workers.